Financial Literacy and Market Discipline On Investment Decisions In The Indonesian Stock Investor Community - Nizar Alam Hamdani; Silviani Wijayanti; Mochamad Romdhon (Entrepreneurship Faculty, Universitas Garut, 2022)
This study examines the effect of financial literacy and market discipline on investment decisions in a community called Indonesian Stock Investors. The research method used is the descriptive analysis method. The population in this study were members of the Indonesian Stock Investor community, with a sample of 98 respondents who were selected using a simple random sampling technique. The analysis technique used in this study is validity and reliability testing, multiple regression analysis and hypothesis testing using SPSS software. Based on the study's results shows that 1) financial literacy affects investment decisions in the Indonesian Stock Investor community. 2) There is an influence of market discipline on investment decisions in the Indonesian Stock Investor community. 3) There is an influence of financial literacy and market discipline on investment decisions in the Indonesian Stock Investor community.